Cleaning and disinfection of surfaces in hospitals. Improvement in quality of structure, process and outcome in the hospitals in Frankfurt/Main, Germany, in 2016 compared to 2014 - Hausemann, Angelika; Grünewald, Miriam; Otto, Ulla; Heudorf, Ursel (German Medical Science GMS Publishing House, 2018)
The cleaning and disinfection of surfaces in hospitals is becoming increasingly important in the multi-barrier approach for preventing infection, in addition to hand hygiene and proper reprocessing of medical devices. Therefore, in 2014, the quality of structure, process and outcome of surface preparation was checked in all hospitals in Frankfurt/Main, Germany. Because of great need for improvements, this monitoring was repeated in 2016. The data are presented in comparison to those in 2014.Methods: All 16 hospitals provided information on the quality of structure. Data on quality of process was obtained through direct observation during cleaning and disinfection of rooms and their bathrooms. Data on quality of result was acquired using the fluorescence method, i.e., marking surfaces with a fluorescent liquid and testing whether this mark has been sufficiently removed by cleaning. The results are compared to those of the 17 hospitals monitored in 2014, before the closing of one of the hospitals.Results: Quality of structure [data from 2014]: In all hospitals, the employees were trained regularly. In 14 (88%) [12; 71%] of those, the foremen had the required qualifications. In 1 (6%) [6; 35%] hospitals, some uncertainty remained concerning the interface of the cleaning and nursing care services. A complete cleaning was reported to take place in 12 (75%) [12; 70%] hospitals on Saturdays and in 4 (25%) [ hospitals on Sundays. Quality of process: During process monitoring, the different surfaces with frequent hand or skin contact were prepared to different extents (91-100%) [70-100%]. Quality of result: 88% [75%] of fluorescent marks were appropriately removed. Conclusion: Compared to 2014, a clear improvement were seen in 2016, especially in the qualification of the foremen and in terms of clearly defining the interface between cleaning and care services as well as the quality of process and outcome. Nevertheless, regarding the growing importance of proper reprocessing of hospital surfaces for prevention of infections and/or colonitions, further improvements are mandatory, including a program for better education of the cleaning staff.